A study on developing speaking skills through techno-driven tasks - Anil, Beena (Brazilian English Language Teaching Journal, 2016)
English is an important language to be learnt in classrooms in most of the developing and third world countries. English language teachers play a vital role in making their students to communicate well in English. They should abreast with new and innovative teaching methodologies in the classroom to enhance the skills of students significantly. This paper is based on the study conducted at five Arts and Science colleges in Chennai, India to test learners’ communicative efficiency and the result is widely applicable to all the second (foreign) language learners. It further discusses the techniques of teaching speaking skills for EL (English Language) learners in second (foreign) language learning countries, like India or Brazil. It highlights the technology-based teaching techniques and methods that help students to develop speaking skills and confidence to face real-life communicative situations